Infinitely many sign-changing solutions to some quasilinear equation involving exponential term. (November 2016) - Aouaoui, Sami
Abstract: In this paper, we prove the existence of infinitely many sign-changing solutions to some quasilinear and elliptic equation whose divergence part contains exponential term. Our main idea consists of the use of the perturbation method together with invariant sets of descending flow in the framework of classical critical point theory.